1996
DOI: 10.1136/jnnp.60.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of leuko-araiosis.

Abstract: Objective-To study the clinical features of leuko-araiosis. Methods-Age matched groups of patients with a CT finding of pure leukoaraiosis (n = 26) and a control group with a normal CT finding (n = 26) were formed (mean ages 78*6 (SD 3.3) v 76 5 (SD 4.6) years; NS).Results-Dementia, vascular dementia, central brain atrophy on CT, disability in activities of daily living and instrumental activities of daily living, urinary incontinence, gait disorder (assistance needed), personality change, and night time confu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…This is in agreement with other clinical studies that have found WMCs to be related to heart failure, atrial fibrillation [26, 27]and hypertension [28, 29]. As both hypotension [30]and low nocturnal BP [31]have also been found to be related to WMCs, the relationship between BP and WMCs appears to be complex.…”
Section: Discussionsupporting
confidence: 79%
“…This is in agreement with other clinical studies that have found WMCs to be related to heart failure, atrial fibrillation [26, 27]and hypertension [28, 29]. As both hypotension [30]and low nocturnal BP [31]have also been found to be related to WMCs, the relationship between BP and WMCs appears to be complex.…”
Section: Discussionsupporting
confidence: 79%
“…The extent of vascular damage has been related to VaD [28]and may play a pivotal role in the reemergence of PRs by a direct or indirect disconnection of subcortical brain structures and deep nuclei from cortical control. White matter lesions have been associated with lower scores in cognitive function tests and with subjective mental decline [29], but their relevance in both degenerative and vascular dementia has yet to be fully elucidated [30]. Leukoaraiosis is reported to be associated with cortical hypometabolism [31]as well as with the reappearance of some primitive reflexes [32], both of which have been considered to result from diffuse corticofugal fiber damage.…”
Section: Discussionmentioning
confidence: 99%
“…They are frequent in VaD and are also found in AD, especially with late onset. In healthy elderly subjects they are associated with subtle neuropsychological [68, 69] and behavioral changes [70]. WMC may contribute to dementia in stroke patients because they indicate an increased risk of stroke recurrence[71], and they lead to a subtle cognitive decline with the possible consequences of stroke lesions and even associated Alzheimer pathology [72].…”
Section: Mechanisms Of Psdmentioning
confidence: 99%